2020
DOI: 10.3390/ijerph17030735
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Built and Online Social Environments on Expression of Dining on Instagram

Abstract: Online social communities are becoming windows for learning more about the health of populations, through information about our health-related behaviors and outcomes from daily life. At the same time, just as public health data and theory has shown that aspects of the built environment can affect our health-related behaviors and outcomes, it is also possible that online social environments (e.g., posts and other attributes of our online social networks) can also shape facets of our life. Given the important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Nowadays, social media such as blogs, websites or social networks such as Twitter, Facebook, Instagram, etc. are increasingly used by the population to acquire health knowledge [ 30 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Nowadays, social media such as blogs, websites or social networks such as Twitter, Facebook, Instagram, etc. are increasingly used by the population to acquire health knowledge [ 30 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The nature of this data can help evade recall or information biases associated with traditional surveys. The often-linked geographic information and time stamps further enable the capture of hyper-local, daily and sub-daily health-related information from behaviours to exposures and other macro-level properties, as well as health outcomes 23,24 . Accordingly, such ubiquitous technologies can provide opportunities to better measure the social determinants of health in a targeted way, by person, location and/or time [21][22][23][24][25] .…”
Section: Machine Learning and Algorithmic Fairness In Public And Population Healthmentioning
confidence: 99%
“…The often-linked geographic information and time stamps further enable the capture of hyper-local, daily and sub-daily health-related information from behaviours to exposures and other macro-level properties, as well as health outcomes 23,24 . Accordingly, such ubiquitous technologies can provide opportunities to better measure the social determinants of health in a targeted way, by person, location and/or time [21][22][23][24][25] . These attributes of person-generated data can complement denominator-based survey and report data that are not available at such high granularity.…”
Section: Machine Learning and Algorithmic Fairness In Public And Population Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring college-aged women's Facebook use and eating disorders, Walker et al found that Facebook intensity, online physical appearance comparison and online "fat talk" is positively associated with eating behaviors [23]. Mhasawade et al studied the role of the built and online social environments in the expression of dining on Instagram [24]. Merchant et al delivered weight loss intervention content through Facebook to college students with the help of a health coach, but whether the health behavior changed is unknown [25].…”
Section: Introductionmentioning
confidence: 99%